Characteristics of coffee as a response to different environmental conditions in Lampung: I. Morphological variations - Erwin Prastowo; Rina Arimarsetiowati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
The coffee growth is considered to depend, partly, on the environmental condition at which they develop to accomplish their both vegetative and generative stages. An exploratory survey aimed at investigating the morphological characteristics of 13 Robusta coffee accessions growing on different environmental conditions, i.e. altitudes, slopes, and micro-climates, in Lampung. Local superior coffee clones were selected from 8 farms to evaluate in terms of their yield components and growth characters. Three key issues are considered to observe quantitatively, i.e. plant components of leaves, branches, and fruits. The qualitative characteristics of leaves and cherries, i.e. colour and shape, were also assessed to support the comparative data analysis. The results show a similarity of ca. 60% of total qualitative variable identified among different accessions. The remaining characters are suggested to be more varying such as flush colour, leaf surface, ripe fruit colour, and stipule shape. Furthermore, a quantitative analysis shows a higher level of similarity for fruit characters, i.e. fruit length, fruit width, and fruit thickness, and to a slightly lower level for leaf characteristics, i.e. leaf length and width, and the number of productive branches. Conversely, part of yield component, such as weight of fruits, may be affected by altitude as some accessions, e.g. number 1 and 8, demonstrating a pronounced character in the principal component analysis. The same analysis reveals that some variables, i.e. fruit weight; leaf and seed; and canopy characteristics, explaining the morphological variation of coffee throughout the accessions. Furthermore, cluster analysis may indicate a possible similarity of coffee morphologies either from area with different or the same environmental conditions. Therefore, it can be concluded that environmental condition variation in Lampung may affect to a lesser extent the morphological characters of Robusta coffee.